EXPLORING THE INFLUENCE OF VIRTUAL LEARNING ON EMPLOYABILITY SKILLS-ISSUES AND SOLUTIONS (International Journal of Food and Nutritional Sciences, 2022)
The expansion of digitalization, the virtual learning centers offering online degree & diploma courses to students that has ensured the continued importance of virtual learning in the classroom and as a self-study-based platform for developing skills. The purpose of this study is to highlight the most important aspects of e-learning that contribute to the acquisition of marketable competencies. Multiple regression analysis was carried out in stages. First-of-its-kind research was conducted. The study included data from 475 pupils in the Vijayapur, Karnataka. In order to ensure that the sample size was sufficient, the researchers used the KMO Bartlett test. According to the findings, the ease with which students may acquire functional and job-specific knowledge through online learning is more important than any other factor when it comes to preparing graduates for the workforce. Teachers should keep the aforementioned things in mind as they design virtual learning activities and modules to help their students acquire job-specific abilities.